Tokens within the meaning of "Heart" in the text the Quran - Paltore, Y. M. (Journal of Oriental Studies, 2016)
This article discusses the concept of "heart" in the light of the text of the holy book Quran. As well as an analysis of the contextof the concept "Heart" with tokens in the meaning of "heart" in the text the Quran.